Animals and the zoogeochemistry of the carbon cycle - Schmitz, Oswald J.; Wilmers, Christopher C.; Leroux, Shawn J.; Doughty, Christopher E.; Atwood, Trisha B.; Galetti, Mauro [UNESP]; Davies, Andrew B.; Goetz, Scott J. (Amer Assoc Advancement Science, 2018)
Predicting and managing the global carbon cycle requires scientific understanding of ecosystem processes that control carbon uptake and storage. It is generally assumed that carbon cycling is sufficiently characterized in terms of uptake and exchange between ecosystem plant and soil pools and the atmosphere. We show that animals also play an important role by mediating carbon exchange between ecosystems and the atmosphere, at times turning ecosystem carbon sources into sinks, or vice versa. Animals also move across landscapes, creating a dynamism that shapes landscape-scale variation in carbon exchange and storage. Predicting and measuring carbon cycling under such dynamism is an important scientific challenge. We explain how to link analyses of spatial ecosystem functioning, animal movement, and remote sensing of animal habitats with carbon dynamics across landscapes.